2008
DOI: 10.1016/j.jmr.2008.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Rapid classification of protein structure models using unassigned backbone RDCs and probability density profile analysis (PDPA)

Abstract: A method of identifying the best structural model for a protein of unknown structure from a list of structural candidates using unassigned 15 N-1 H residual dipolar coupling (RDC) data and probability density profile analysis (PDPA) is described. Ten candidate structures have been obtained for the structural genomics target protein PF2048.1 using ROBETTA. 15 N-1 H residual dipolar couplings have been measured from NMR spectra of the protein in two alignment media and these data have been analyzed using PDPA to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…EPAR then computes the average value for the leftmost matrix in Eq. (3) (Bansal et al 2008) for each set of corresponding vectors across the domains. Because the symmetric axis of the dimer must be collinear with one of the 3 axes of PAF, this step is not required for a perfectly symmetric homo-dimer, as RDCs for both subunits are identical.…”
Section: Methodsmentioning
confidence: 99%
“…EPAR then computes the average value for the leftmost matrix in Eq. (3) (Bansal et al 2008) for each set of corresponding vectors across the domains. Because the symmetric axis of the dimer must be collinear with one of the 3 axes of PAF, this step is not required for a perfectly symmetric homo-dimer, as RDCs for both subunits are identical.…”
Section: Methodsmentioning
confidence: 99%
“…When residual dipolar couplings are collected in multiple alignment media, the RDC data in each medium that corresponds to the same interacting vector can be paired using chemical shift data [18]. As previously observed [14,29,31,38], the information gained by correlating data from two media is much richer than the data that can be gleaned from a separate analysis of each single channel of data.…”
Section: Background and Theorymentioning
confidence: 99%
“…Applications of the RDC data include the study of challenging biomolecules such as membrane proteins [14], carbohydrates [57], and DNA/RNA [811] to name a few. Recent advances include structure determination from multiple alignment media [1215], reconstruction of the relative order tensors from unassigned RDC data [15,16], and identification of homologous structures [17,18] from unassigned RDC data. These elaborate methods utilize RDC data collected from multiple alignment media, sometimes requiring data from as many as 5 or more alignment media [13,1921].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods generally utilize a very small portion of RDCs (N-H from one or two alignment media) in order to guide the computational modeling of structures, which have produced very exciting results. A number of other research efforts 10,11,41,4850 , have demonstrated the possibility of De Novo structure determination based on slightly more experimental data than what is required by hybrid approaches. However these methods employ stochastic search approaches that do not provide any upper bound in computation time or quality of the final structure.…”
Section: Introductionmentioning
confidence: 99%